2000
DOI: 10.1002/1096-8628(200022)97:2<136::aid-ajmg5>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prader-Willi and Angelman syndromes: Sister imprinted disorders

Abstract: Prader-Willi syndrome (PWS) and Angelman syndrome (AS) are clinically distinct complex disorders mapped to chromosome 15q11-q13. They both have characteristic neurologic, developmental, and behavioral phenotypes plus other structural and functional abnormalities. However, the cognitive and neurologic impairment is more severe in AS, including seizures and ataxia. The behavioral and endocrine disorders are more severe in PWS, including obsessive-compulsive symptoms and hypothalamic insufficiency. Both disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(168 citation statements)
references
References 95 publications
(124 reference statements)
2
157
0
9
Order By: Relevance
“…52 UPD, which arises when an individual inherits two copies of a chromosome pair from one parent and no copy of the other parent, can result in rare recessive disorders, or developmental problems because of the effects of imprinting. 53 Examples of genetic diseases linked to UPD include the Prader -Willi syndrome (MIM 176270), Angelman syndrome (MIM 105830), BeckwithWiedemann syndrome (MIM 130650) and Silver -Russell syndrome (MIM 180860). SNP array analysis is able to detect uniparental isodisomy and uniparental heterodisomy (when both parents are included in the experiment), but the interpretation of new UPD regions is difficult and further research is required to confirm the clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 UPD, which arises when an individual inherits two copies of a chromosome pair from one parent and no copy of the other parent, can result in rare recessive disorders, or developmental problems because of the effects of imprinting. 53 Examples of genetic diseases linked to UPD include the Prader -Willi syndrome (MIM 176270), Angelman syndrome (MIM 105830), BeckwithWiedemann syndrome (MIM 130650) and Silver -Russell syndrome (MIM 180860). SNP array analysis is able to detect uniparental isodisomy and uniparental heterodisomy (when both parents are included in the experiment), but the interpretation of new UPD regions is difficult and further research is required to confirm the clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have already mentioned the partial replacement of conventional karyotyping by molecular karyotyping. 53,57 In addition, Koolen et al 29 described a workflow for the clinical interpretation of CNVs in individuals with MR. Our results show that high-density SNP arrays can be successfully used as a tool for the detection of CNVs, low-level mosaicism and copy number neutral abnormalities. Their high resolution and commercial availability make them attractive to implement in a routine diagnostic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 here++++++++++++ Within a number of the studies, some reported clinical characteristics such as speech difficulties, ataxic gait and protruding tongue were often placed in different categories. For example ataxic gait has been categorised as a musculoskeletal (Zori, Hendrickson, Woolven, Whidden, Gray & Williams, 1992) or neurological phenomenon (Dorries, Spohr & Kunze, 1988) or behaviour characteristic (Cassidy, Dykens, Williams, 2000). For the purpose of this review, speech difficulties, ataxic gait and protruding tongue will not be categorised as behaviours, consistent with studies by Zori et al, (1992), Clayton-Smith and Laan (2003), and Clayton-Smith (1992).…”
Section: Behavioural Phenotype Of Angelman Syndromementioning
confidence: 94%
“…One consequence of repeat deletion is failure to assemble and correctly segregate chromosomes during meiosis and mitosis 79 . Microdeletion in areas of SAT overlap, such as those observed in 70% of human Angelman and Prater-Willi syndromes 80 , may have a similar basis, as may chromosomal loss during oncogenesis. Deletion of retroelements from inverted repeats, such as those found in the human Y chromosome 81 , may be favored by the enhanced transcription and chromatin remodeling occurring during spermatogenesis 82 .…”
Section: Rna-directed Rewriting Of Dnamentioning
confidence: 99%